PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MODEL PEMBELAJARAN THINK-PAIR-SHARE (TPS) SISWA KELAS VIII B SMPN 2 NGLIPAR GUNUNG KIDUL TAHUN AJARAN 2013/2014 - Deni Prasetyo; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aimed to describe (1) the increase in activity of students in reading comprehension with Think-Pair-Share (TPS) learning model and (2) describe an increase in the ability of students in reading comprehension with TPS learning model At VII B rade Students of Junior High School 2 Nglipar Gunung Kidul Academic Year 2013/2014. This study is an action research which is implemented in cycles. After cycle II, more than 80% students finish individually. Methods of data collection in this study using observation, test, and interview. The results of this study indicate that (1) TPS learning model can improve student learning activity of reading comprehension in the learning process and (2) TPS learning model can improve the ability of students in teaching reading comprehension.